The Relationship Between Public Health Insurance Patient Satisfaction (JAMKESMAS) and Visits Return Patients to Pedada Health Center - Nurul Aziza; Nova Mega Rumana; Radella Hervidea; Dewi Woro Astuti; Adhi Nurhartanto (International Journal Labs, 2026)
Patient satisfaction is a key indicator for assessing healthcare quality and influences healthcare utilization behavior, including patient revisits. The Public Health Insurance Program (JAMKESMAS) aims to provide healthcare access for the poor and underprivileged; however, its implementation still faces various challenges that can affect patient satisfaction levels. This research aimed to determine the relationship between JAMKESMAS patient satisfaction and patient revisits to the Pedada Health Center, Pesawaran Regency, in 2025. This study employed an analytical cross-sectional design. A total of 65 JAMKESMAS patients were selected using total sampling. Data on satisfaction were collected through a questionnaire, while revisit behavior was observed using visit logs. Univariate and bivariate analyses were performed using the Chi-square test (? = 0.05). Results indicated that the majority of JAMKESMAS patients were dissatisfied (55.4%) and irregular in their revisit behavior (75.4%). The results of the statistical test showed a significant relationship between JAMKESMAS patient satisfaction and patient revisits to the Pedada Health Center, Pesawaran Regency, in 2025 (p-value = 0.012). An Odds Ratio value of 5.647 indicates that dissatisfied JAMKESMAS patients have a greater likelihood of irregular revisits compared to satisfied patients. It can be concluded that JAMKESMAS patient satisfaction is significantly related to patient revisits. Therefore, improving the quality of healthcare services at the Puskesmas is essential to increase patient satisfaction and encourage regular revisits.